Efecto del entrenamiento concurrente en las fibras musculares de ratas wistar sometidas a Dietas normal e hipercalórica - Castoldi, Robson Chacon; Aleixo, Paulo Henrique; Pereira, Alysson Christian Jesus; Ferreira, Sergio Ruiz; Garcia, Thiago Alves [UNESP]; Ozaki, Guilherme Akio Tamura [UNESP]; Koike, Tatiana Emy; Júnior, Danilo Antônio Corrêa Pinto; Seraphim, Patrícia Monteiro [UNESP]; Belangero, William Dias; Filho, José Carlos Silva Camargo [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2017)
To analyze the effects of concurrent training (CT) on the muscle fibers of Wistar rats submitted to standard and hypercaloric diets. In total, 40 rats were used, divided into 4 groups: Sedentary Group (GS); Exercise Group (GE), Obese Sedentary Group (OS) and Obese Exercise Group (OE). The animals performed a CT protocol consisting of: muscle strength training and aerobic training, carried out 3 times a week for 45 days. The smallest diameter of muscle fibers (MDF) was analyzed to evaluate muscle hypertrophy. It was observed that the OE group presented a significant decrease in MDF, compared to the OS group (OE=77.41 mm vs. OS=98.58 mm). In addition, the animals that performed CT demonstrated muscle hypertrophy (GE=74.39 mm vs. GS=72.13 mm). In conclusion, the CT with a standard diet promoted an increase in MDF while CT with a hypercaloric diet resulted in a decrease.
Effects of concurrent training on muscle fibers of wistar rats submitted to standard and hypercaloric diets
Keywords: Hypertrophy; Muscles; Obesity; Rats; Training